Experimental test to analyze and evaluate the exergy and energy efficiency of the AHU in the Waterchiller system - Bui, Van Cuong; Nguyen, Duc Khuyen; Phan, Thanh Nhan (EAI Endorsed Transactions on Sustainable Manufacturing and Renewable Energy, 2025)
Experimental study to determine the impact of changing AHU operating parameters on exergy and energy efficiency in the water chiller system. The study used both an experimental method and theoretical calculations, with a Trane-brand chiller system with a cooling capacity of 25,3 kW. The results showed that when the supply air temperature increased from 295 K to 299 K, the heat exchanger's exergy consumption ( ) decreased from 0.2 kW to about 0.05 kW. The exergy consumption of the heat exchanger ( ) and the exergy flow of the return air to the AHU ( ) were almost constant, maintained at about 0.95 kW and 0.8 kW, showing that the efficiency of the heat exchanger and the exergy of the ambient air were relatively stable, not much affected by changes in ambient temperature. When the inlet water temperature ( ) increases from 284 K to 289 K. The water exergy flow ( ) decreases linearly from about 1.3 kW to about 0.8 kW. In addition, this study also evaluates the impact of changing the chilled water pump frequency and air flow rate on energy efficiency. The results indicate that the optimal operating point is not at the maximum frequency but at about 45 Hz, at which the cooling capacity reaches 7,764 kW.
Keywords: Water chiller; Performance; Energy consumption; Exergy; Heat transfer